Simple DNA extraction method for SSR-PCR analysis from different tissues of Tapiscia sinensis, an endangered plant species - Zhou, Xiao-Jun; Yan, Rong-Shan; Xu, Ya-Nan; Zou, Da-Wei; Zhao, Peng; Liu, Wen-Zhe (The Indian Journal of Genetics and Plant Breeding, 2016)
A simple and rapid method to process different tissues of Tapiscia sinensis for effective plant DNA extraction were established in the study. DNA quality and yield obtained from bark, leaves and seeds were evaluated by Eppendorf BioPhotometer and SSR-PCR analysis. The results indicated that extracted genomic DNA based on the established method was sufficient for SSR-PCR profiling of different tree tissues. Hence, the sample treatment and extraction method can be used for SSR-PCR applications in tree genetic and molecular analysis research.